SEMANTICS AND PRAGMATICS IN POETRY : A STUDY ON WILLIAM STANLEYâS THE UNWRITTEN, PABLO NERUDAâS UNTITLED, AND ANA MARIA IZAâS FORMULA - ., Kustinah (MAGISTRA, 2016)
This paper aims at finding out whether literary interpretation produces an effect of pragmaticsand semantics as a result of processes of a reading-act. As an effort to get the answer, the writer of this writinganalyzes three poems. The first is The Unwritten by William Stanley (1927-...), the second is Untitled by PabloNeruda (1904-1973), and Formula by Ana Maria Iza. The technique used would be a careful study on each ofinterpretation through the three poems . The discussion will view the possibilities of pragmatics and semanticssense in those three poems.The core idea of this article came from Wolfgang Iser who wrote The Act of Reading (1987). Hebelieved that a literary text can only produce a response when it is read. It is virtually impossible to describe thisresponse without also analyzing the reading process (1987:ix). Referring to that quotation, this paper will presentdetailed proces of reading the above three poems and the process of interpretation thus encoding the pragmaticsand semantics point of view.Key-words : reading-act, poetry, pragmatics, semantics